Tumor-Targeted Human T Cells Expressing CD28-Based Chimeric Antigen Receptors Circumvent CTLA-4 Inhibition. - Maud Condomines (PLoS ONE, 2015)
Adoptive T cell therapy represents a promising treatment for cancer. Human T cells engineered to express a chimeric antigen receptor (CAR) recognize and kill tumor cells in a MHC-unrestricted manner and persist in vivo when the CAR includes a CD28 costimulatory domain. However, the intensity of the CAR-mediated CD28 activation signal and its regulation by the CTLA-4 checkpoint are unknown. We investigated whether T cells expressing an anti-CD19, CD3 zeta and CD28-based CAR (19-28z) displayed the same proliferation and anti-tumor abilities than T cells expressing a CD3 zeta-based CAR (19z1) costimulated through the CD80/CD28, ligand/receptor pathway. Repeated in vitro antigen-specific stimulations indicated that 19-28z+ T cells secreted higher levels of Th1 cytokines and showed enhanced proliferation compared to those of 19z1+ or 19z1-CD80+ T cells. In an aggressive pre-B cell leukemia model, mice treated with 19-28z+ T cells had 10-fold reduced tumor progression compared to those treated with 19z1+ or 19z1-CD80+ T cells. shRNA-mediated CTLA-4 down-regulation in 19z1-CD80+ T cells significantly increased their in vivo expansion and anti-tumor properties, but had no effect in 19-28z+ T cells. Our results establish that CTLA-4 down-regulation may benefit human adoptive T cell therapy and demonstrate that CAR design can elude negative checkpoints to better sustain T cell function.